PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MINUMAN BERALKOHOL PADA OUTLET VINES ONE BELPARK DI JAKARTA SELATAN - Crista Angtolis, Yolanda; Irmal (Journal of Research and Publication Innovation, 2024)
This research aims to find out the impact of service quality and price on the purchasing decisions of alcoholic beverages at the Vines One Belpark outlet in South Jakarta, both partially and simultaneously. This research employs associative and quantitative methods. The population of this study consists of consumers of Vines One Belpark in South Jakarta. The research sample includes 97 respondents, determined using the Slovin formula. Data collection was conducted using questionnaires, and data analysis techniques included validity tests, reliability tests, classical assumption tests, linear regression tests, correlation coefficient tests, determination coefficient tests, partial hypothesis tests (t-test), and simultaneous hypothesis tests (f-test) with the help of SPSS software version 25. The results of the study indicate that (1) Service quality affects purchasing decisions with the regression equation Y = 11.215 + 0.737 X, a correlation coefficient value of 0.715, a determination coefficient value of 0.512, significantly influencing purchasing decisions as evidenced by the t-value > t-table (9.979 > 1.985) with a significance value of 0.05 or (0.000 < 0.05), (2) Price affects purchasing decisions with the regression equation Y = 10.133 + 0.980 X2, a correlation coefficient value of 0.818, a determination coefficient value of 0.669, significantly influencing purchasing decisions as evidenced by the t-value > t-table (13.871 > 1.985) with a significance value of 0.05 or (0.000 < 0.05), (3) Service quality and price simultaneously affect purchasing decisions with the regression equation Y = 7.214 + 0.212 (X1) + 0.790 (X2), a correlation coefficient value of 0.829, a determination coefficient value of 0.686, significantly influencing purchasing decisions as evidenced by the F-value > F-table (102.911 > 3.093) with a significance value of < 0.05 or (0.000 < 0.05). It can be concluded that service quality and price simultaneously have a positive and significant effect on purchasing decisions at the Vines One Belpark outlet in South Jakarta.